2014
DOI: 10.1111/1574-6968.12384
|View full text |Cite
|
Sign up to set email alerts
|

DsbM affects aminoglycoside resistance inPseudomonas aeruginosaby the reduction of OxyR

Abstract: DsbM is a novel disulfide oxidoreductase that affects aminoglycoside resistance in Pseudomonas aeruginosa by an OxyR-regulated process. However, the detailed mechanism of interaction between DsbM and OxyR had not yet been elucidated. In this study, we expressed DsbM in Escherichia coli and showed that DsbM can oxidize and reduce disulfide. We also used a yeast two-hybrid assay to identify interactions between DsbM and OxyR. A subsequent GSH oxidation experiment revealed that DsbM could alter both the oxidized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Given the cellular location of DsbM, DsbM should acquire its reducing power from the cytosolic glutathione pool. Considering both the results in this paper and previously reported data on the reduction of DsbM by OxyR (Li et al, 2014), we propose an mechanism of action for DsbM in which the oxidized OxyR and the reduced glutathione are shuttled on the glutathione-binding site (or putative substrate-binding region) of DsbM (Fig. 7).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Given the cellular location of DsbM, DsbM should acquire its reducing power from the cytosolic glutathione pool. Considering both the results in this paper and previously reported data on the reduction of DsbM by OxyR (Li et al, 2014), we propose an mechanism of action for DsbM in which the oxidized OxyR and the reduced glutathione are shuttled on the glutathione-binding site (or putative substrate-binding region) of DsbM (Fig. 7).…”
Section: Discussionsupporting
confidence: 73%
“…In the absence of hydrogen peroxide, OxyR returns to its reduced form (inactive state) through cellular reducing agents, such as glutathione (Toledano et al, 1994;Storz & Tartaglia, 1992;Jo et al, 2015;Choi et al, 2001). The interaction between DsbM and OxyR was confirmed through a yeast two-hybrid screen, and DsbM showed increased reduction of OxyR in P. aeruginosa (Li et al, 2014;Wang et al, 2012). In particular, it was reported that aminoglycoside resistance was increased in P. aeruginosa when dsbM was deleted.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Suggesting a possible connection between GSH and Dsb proteins in the periplasm, a new Dsb member, DsbM, was described in Pseudomonas aeruginosa which has structural similarity to DsbA and, to a lesser extent, to the Trx-domain of DsbC (134). While DsbM is cytoplasmic, it was reported to have a GSHdependent reductase activity against an oxidized OxyR mechanism of direct regulation of OxyR by reduction (135,136), suggesting that well-known Dsb proteins such as DsbA and DsbC may have GSH-dependent mechanisms that are still undisclosed. The dsbC gene is in a bi-cistronic operon with the downstream gene recJ, which encodes a 5′→3′ exonuclease.…”
Section: Isomerization Of Mismatched Disulfides and Protection Of Lonmentioning
confidence: 99%